New aplysiatoxin derivatives from the Okinawan cyanobacterium Moorea producens - Nagai, Hiroshi; Watanabe, Minami; Sato, Shingo; Kawaguchi, Mioko; Xiao, Yue-Yun; Hayashi, Kazutaka; Watanabe, Ryuichi; Uchida, Hajime; Satake, Masayuki (Tetrahedron, 2019)
The marine cyanobacterium Moorea producens is a rich source of diverse compounds that possess a variety of biological activities. In the present study, eight new aplysiatoxin derivatives, namely 6, 8–13, and 15, along with aplysiatoxin (1), debromoaplysiatoxin (2), 3-methoxyaplysiatoxin (3), anhydroaplysiatoxin (4), anhydrodebromoaplysiatoxin (5), oscillatoxin B2 (7), and 30-methyloscillatoxin D (14) were isolated and identified from the Okinawan M. producens. In cytotoxicity and diatom growth inhibition tests, the fifteen compounds tested (1–15) showed moderate or no activity at a concentration of 10 μg/mL. [Display omitted]